Determinants of cerebral palsy among under-5 children (Bangladesh Medical Journal, 2016)
Cerebral palsy (CP) is one of the leading causes of childhood disability worldwide, with the greatest burden found in the developing countries of the world. This hospital based case-control study was conducted from January 2010 to June 2010 to find out the determinants of cerebral palsy among under-5 children. The study was conducted among 76 diagnosed cerebral palsy cases with 76 children considered as control group from the same institute. Study suggested that, children with male sex were four times more likely to have cerebral palsy than the female child. There were more than 2.5 times more chance of developing cerebral palsy among the parents who had consanguineous marriage. In case of home delivery there were 2.25 times more chance of developing cerebral palsy than those had the hospital delivery. Among the mothers of the cases who were suffering from problem during delivery, 47.5% had prolong labour during delivery, 25.0% had premature rupture of membrane and 20.0% had breech presentation.There were 33 times more risk of developing cerebral palsy among the premature baby than the term birth. There were 12.5 times more chance of developing cerebral palsy among the low birth weight child than the of normal weight child. This study concluded that, greater knowledge and understanding on cerebral palsy is required to enhance decision-making processes about the affected children.Bangladesh Med J. 2015 Jan; 44 (1): 3-7